The Influence of the Audio-Lingual Method in Improving the Students' Vocabulary at SMA Negeri 21 Makassar - Tria Ali; Abidin Pammu; Nasmilah Nasmilah (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study aims to find out the influence of the audio-lingual method (AML) in learning student vocabulary. The study uses a quantitative methodology to assess students' proficiency with the audio-lingual method (AML) in vocabulary learning. The audio-lingual Method (AML) arose after the aural-oral approach was devised in 1939 at the first English language Institute at the University of Michigan, United States by Charles Fries. The population of this study is first-grade students of SMA Negeri 21 Makassar 2023 There were five classes consisted 33 students per class. Moreover, The collecting data in this research are vocabulary tests and questionnaires. A vocabulary test is the instrument to find out whether dialogue can improve their vocabulary, while a questionnaire is an instrument for knowing the students' responses. The result of this study is Using the audio-lingual Method (ALM), students' pre-test and post-test scores on their vocabulary tests increased. The quantity of data, where 40% of the data showed that the student's scores improved as a result of using the audio-lingual method (ALM) in their English learning. In particular, with the growing influence of technology, vocabulary learning should be easier to be creative with, as there are many learning models that teachers can be inspired by to make their classes suit students' learning preferences, especially in this era.